SOME ASPECTS OF DISTILLATE PRODUCTION FROM JERUSALEM ARTICHOKE TUBERS.PART 1. DYNAMIC OF DISTRIBUTION OF VOLATILE COMPONENTS BY DISTILLATION OF FERMENTED WORT - Krikunova L.N. (Техника и технология пищевых производств, 2017)
Topinambour or Jerusalem artichoke is one of the promising raw materials for production of high quality alcoholic beverages in the Russian Federation. Jerusalem artichoke is of interest as a raw material for production of alcoholic beverages because of its wide prevalence, high cold resistance and flexibility to environmental conditions. In addition, the tubers of Jerusalem artichoke are rich in potentially fermentable carbohydrates. The yield of alcohol from Jerusalem artichoke is in average 1.5 - 3.5 times higher than that from wheat or potato. In this study, the dynamics of distribution of volatile compounds during distillation of fermented wort of Jerusalem artichoke has been investigated. The way the method of preparation of raw materials for distillation influences this process has also been determined. As a result of the research common regularities of distribution of individual volatile components in fractions during distillation of fermented wort of Jerusalem artichoke have been revealed. The obtained data allowed us to define the extremum points for acetaldehyde, ethyl acetate, pure spirit of best quality, phenylethyl alcohol and enanth ester which largely determine sensory profile of spirits. It has been shown that the distribution of acetaldehyde, ethyl acetate, methanol and higher alcohols does not depend on the method of preparation of raw materials for distillation and the time of fermentation. It has been established that the method of preparation of raw materials affects the distribution of phenylethyl alcohol and enanth ester during distillation. The use of one-stage method of Jerusalem artichoke preparation makes it possible to obtain distillate of higher concentration of enanth ester from 7 % to 30 % thus positively affecting the flavor and taste of the distillate.